Determinants of Shari’ah gold investment behaviour: the case of Penang, Malaysia - Hani Amirah Juisin; Muhammad Amir Syazwan Mohd Sayuthi; Hanudin Amin; Imran Mehboob Shaikh (Emerald Group Publishing Limited, 2023)
Purpose – Gold investment is one of the essential long-term investments for many to diversify their investment portfolios. Muslims are continuously looking for halal products and services in any aspect of life and one of them is Shari’ah gold investments (SGI). However, evidence pertinent to Muslims’ behaviour towards Shari’ah gold is somewhat inconclusive and for that, a new empirical investigation is needed to reduce the gap, at best. Hence, the purpose of this study is to study factors determining SGI behaviour in Penang, Malaysia. Design/methodology/approach – By using the Islamic theory of consumer behaviour (ITCB), this study examines the determinants of the SGI behaviour. The questionnaire survey was distributed and the data gathered was analysed using partial least square structural equation modeling. Findings – All hypothesised hypotheses were instrumental in explaining the factors determining SGI behaviour in the context of Penang, Malaysia. Research limitations/implications – This study has at least two limitations, namely, confined generalisations of the variables used and the limited context of the research conducted. Practical implications – This study sheds light on the determinants influencing SGI behaviour, at best. Originality/value – This study is original in terms of its final output that enlightens the significant effects of iman, Islamic altruism, maqasid consumer index on the behaviour of investors on Shari’ah gold within the ITCB’s context along with integrated religious satisfaction. Keywords Islamic theory of consumer behaviour, Muslims, Penang, Malaysia, Shari’ah gold investment Paper type Research paper